Rethinking Pre-Crime Surveillance versus Privacy in an Increasingly Insecure World: Imperative Expediency - Olugasa, Olubukola (2017)
Till date the United States of America has not overcome the 9/11 shock despite her efficient police and intelligence network. Nigerians would have perhaps saved the horror of the Boko Haram kidnap of the 276 innocent school girls in Maiduguri. Australians in Sydney would perhaps have prevented the death of two citizens in the hand of a man with known history of violence and crime at "the siege in Martin Place" had proper pre-emptive measures been taken. Less than 24 hours to that of Sydney Pakistan suffered its most horrifying attack in the hands of the Pakistan Taliban, causing a massacre of about 126 innocent children. Next, France became the victim. Some world leaders gathered to conduct a solidarity march and protest against terrorism. The clamour among scholars who hold fastidiously to the preservation of privacy against the quest for crime prevention surveillance in an insecure world today may be very rational and worthy of merits. But is it expedient? It appears the various democratic jurisdictions agitate against crime prevention surveillance in a manner detrimental to the same security they concertedly desire to provide for the citizens. Law enforcement agencies seek efficiency, relevance and confidence of the citizens in their role in society but it seems the same society backed by scholars would not listen? What message are we passing to the law enforcement agencies? Who should the population trust more; the citizens or the law enforcement officers? Whose privacy is the state protecting? Whose security is the state obliged to protect? Could the resistance to crime prevention surveillance tie the hands of the state law enforcement and inadvertently provide opportunities for criminals and terrorists? What is the way forward? These are the questions this paper intends to discuss in the light of recent global events of security breaches. Key Words: Adversarial system, Privacy, Surveillance, Criminal justice, Crime prevention, Crime control, Securit